First-principles investigation of BiVO3 for thermochemical water splitting. (15th January 2019) - Ong, Marc; Campbell, Quinn; Dabo, Ismaila; Jishi, Radi A.
Abstract: Thermochemical water splitting is a promising clean method of hydrogen production of high relevance in a society heavily reliant on fossil fuels. Using evolutionary methods and density functional theory, we predict the structure and electronic properties of BiVO3 . We build on previous literature to develop a framework to evaluate the thermodynamics of thermochemical water splitting cycles for hydrogen production. We use these results to consider the feasibility of BiVO3 as a catalyst for thermochemical water splitting. We show that for BiVO3, both the thermal reduction and gas splitting reactions are thermodynamically favorable under typical temperature conditions. We predict that thermochemical water splitting cycles employing BiVO3 as a catalyst produce hydrogen yields comparable to those of commonly used catalysts. Highlights: Stable BiVO3 crystal and electronic structures found using genetic algorithms. Vacancy energy of BiVO3 found as 3.72 eV, comparable to values in CeO2 . Framework for determining favorable thermochemical water splitting temperatures. Predicted yield for BiVO3 of 1.5 μmol/g and 0.03 μmol/g for TTR of 1750 K and 1500 K.